ANCIENT INDIA: KINGDOM AND TERRITORY - Vasava, Bhumika B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ancient India is renowned for its rich history, characterized by a diverse array of kingdoms and territories. This period, spanning over millennia, saw the rise and fall of numerous dynasties, each uniquely contributing to the cultural, political, and social landscape of the subcontinent. Key kingdoms, such as the Mauryas, Guptas, Cholas, and Pandyas, played pivotal roles in shaping India’s legacy. Territorial expansions were often marked by strategic conquests, alliances, and the spread of art, religion, and philosophy. This study explores the intricate dynamics of power, governance, and territorial boundaries in ancient India, highlighting how these factors collectively forged the nation’s historical identity.